2020
DOI: 10.21203/rs.3.rs-36964/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploiting an early warning nomogram for predicting the risk of ICU admission in COVID-19 patients: A multi-center study in China

Abstract: Background Novel coronavirus disease 2019 (COVID-19) is a global public health emergency. Here, we developed and validated a practical model based on the data from a multi-center cohort in China for early identification and prediction of which patients will be admitted to the intensive care unit (ICU).Methods Data of 1087 patients with laboratory-confirmed COVID-19 were collected from 49 sites between January 2 and February 28, 2020, in Sichuan and Wuhan. Patients were randomly categorized into the training an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…We report the characteristics and associated outcomes of patients seen in the EDs in our hospital system during the initial phase of the COVID-19 pandemic in Seattle. 8,12,16,17,[32][33][34][35] We found that vital signs were strong predictors of ICU admission, We report a higher proportion of patients who were admitted to the ICU than prior cohorts. 5,7,9,11 Given that our mortality rate was similar to prior cohorts, this is likely a reflection of our hospital system during the time these data were gathered.…”
Section: Discussionmentioning
confidence: 57%
“…We report the characteristics and associated outcomes of patients seen in the EDs in our hospital system during the initial phase of the COVID-19 pandemic in Seattle. 8,12,16,17,[32][33][34][35] We found that vital signs were strong predictors of ICU admission, We report a higher proportion of patients who were admitted to the ICU than prior cohorts. 5,7,9,11 Given that our mortality rate was similar to prior cohorts, this is likely a reflection of our hospital system during the time these data were gathered.…”
Section: Discussionmentioning
confidence: 57%
“…In another study, a regression analysis showed that Creactive protein (CRP) was significantly associated with aggravation of non-severe COVID-19 patients, with an area under the curve of 0.844 (95% confidence interval, 0.761-0.926) and an optimal threshold value of 26.9 mg/L [16]. In a Spanish study, COVID-19 patients with normal levels of lymphocytes or mild lymphopenia, imbalanced lymphocyte subpopulations were early markers of in-hospital mortality [26].…”
Section: Introductionmentioning
confidence: 99%